The Use of Local Food Products and Medicinal Plants for the Regulation of Liver Functions in Pesticide Poisoning in the Experiment (International Journal of Psychosocial Rehabilitation, 2020)
It is known that all pesticides possess hepatotropic properties even in small doses, which makes the problem of protecting the liver from the toxic effects of pesticides one of the urgent regional medical and social problems.